2010
DOI: 10.1590/s0102-695x2010005000006
|View full text |Cite
|
Sign up to set email alerts
|

Flavanones from aerial parts of Cordia globosa (Jacq.) Kunth, Boraginaceae

Abstract: RESUMO: "Flavanonas isoladas das partes aéreas de Cordia globosa (Jacq.) Kunth (Boraginaceae)". A análise fitoquímica das partes aéreas de Cordia globosa, coletadas no município de Picuí, PB, Brasil, resultou no isolamento e identificação estrutural da 7,4'-dimetilnarigenina (0,025 g) e eriodictiol (0,015 g). Estas duas flavanonas são as primeiras agliconas, desta classe, isoladas no gênero Cordia.Unitermos: Cordia globosa, Boraginaceae, flavanonas, 7,4'-dimetilnarigenina, eriodictiol. ABSTRACT:The phytochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…The position of this additional methyl group was also confirmed by LREIMS analysis due the fragments at m/z 166 (C 8 H 6 O 4 ) and 134 (C 9 H 10 O), formed due to retro-Diels-Alder rearrangement. Comparison with spectral data with those described in the literature (Agrawal, 1989;Silva et al, 2009), allowed the identification of 3 as 5-hydroxy-7,4 0 -dimethoxyflavanone (sakuranetin 4 0 -methyl ether).…”
Section: Resultsmentioning
confidence: 80%
“…The position of this additional methyl group was also confirmed by LREIMS analysis due the fragments at m/z 166 (C 8 H 6 O 4 ) and 134 (C 9 H 10 O), formed due to retro-Diels-Alder rearrangement. Comparison with spectral data with those described in the literature (Agrawal, 1989;Silva et al, 2009), allowed the identification of 3 as 5-hydroxy-7,4 0 -dimethoxyflavanone (sakuranetin 4 0 -methyl ether).…”
Section: Resultsmentioning
confidence: 80%
“…Previous investigations led to the isolation of cytotoxic monoterpenes from the roots of C. curassavica and C. globosa [3,4], meroterpenoid naphthoquinones from the roots of C. linnaei [6], anti-inflammatory sesquiterpenes from C. trichotoma and C. verbenacea [5,22], abietane type diterpenes from C. latifolia [23], triterpenes from C. spinescens, C. multispicata and from C. verbenacea [24,25,26], saponins from C. piauhiensis [27,28,29],antifungal and larvicidal phenylpropanoid derivatives from the root bark of C. alliodora [2], essential oils from C. cylindrostachya [30], flavonoids from C. dichotoma , C. obliqua and from the flowers of C. dentate [31,32,33], flavonones from the aerial parts of C. glosbosa , C. oblique , C. francisci , C. martinicensis , C. myxa and C. serratifolia [34], pyrrolizidine alkaloids from C. myxa and glutarimide alkaloids from C. globifera [35,36], lignan from C. rufescens [37], rosmarinic acid from C. americana and different aromatic compounds from C. latifolia and C. dentate [38,39,40]. The present study reported the isolation of compounds 1– 9 from the aerial parts of C. sinensis .…”
Section: Resultsmentioning
confidence: 99%
“…0 -Dihydroxy-3,7,4 0 -trimethoxyflavone (113) C. multispicata [79] Leaves Flavanone Eriodictyol (114) C. globosa [130] Aerial parts Distylin-3-xyloside (115) C. obliqua [131] Seed Narigenin-4 0 ,7-dimethyl ether (116) C. globosa [132] Aerial part Hesperetin-7-O-b-L-rhamnopyranoside C. obliqua [79] Root Hesperetin-7-rhamnoside C. obliqua [79,80] Seed 3 0 ,5-Dihydroxy-4 0 -methoxy flavanone-7-O-a-L-rhamnopyranoside C. obliqua [118] Stem bark Flavanonol 5,7-Dimethoxytaxifolin-3-O-a-L-rhamnopyranoside (117) C. obliqua [133] Root Taxifolin 3,5-dirhamnoside C. obliqua [80,118] Seed Isoflavone 7,4 0 -Dihydroxy-5 0 -carboxymethoxy isoflavone (118) C. verbenacea [134] Leaves 7,4 0 -Dihydroxy-5 0 -Me isoflavone (119) C. verbenacea [134] Leaves Retusin (120) C. multispicata [85] Leaves 2.9. Lignans Rufescidride (121) C. rufescens [130] Stem Rufescenolide (122) C. rufescens [130] Stem…”
Section: Abietane Diterpenesmentioning
confidence: 99%